A giant negative electrocaloric effect in Eu-doped PbZrO3 thin films. Issue 16 (11th April 2016) - Ye, Mao; Li, Tao; Sun, Qiu; Liu, Zhikai; Peng, Biaolin; Huang, Chuanwei; Lin, Peng; Ke, Shanming; Zeng, Xierong; Peng, Xiang; Chen, Lang; Huang, Haitao
Abstract : A negative electrocaloric effect (ECE) in 4 mol% Eu-doped PbZrO3 antiferroelectric (AFE) thin films prepared by using a sol–gel method is investigated via indirect measurements. Abstract : A negative electrocaloric effect (ECE) in 4 mol% Eu-doped PbZrO3 antiferroelectric (AFE) thin films prepared by using a sol–gel method is investigated via indirect measurements. Temperature dependent P – E hysteresis loops were measured. A giant negative electrocaloric temperature change of over 6.6 K was observed. These results raised hopes for the enhancement of the cooling efficiency in combination with positive ECE.